PERBANDINGAN CERITA RAKYAT SASAK DAN SAMAWA: UPAYA MEMAHAMI MASYARAKAT SASAK DAN SAMAWA - Syaiful Bahri (MABASAN, 2018)
In this paper, there are two problems to be answered, namely are (1) the comparison between Sasak and Samawa folktales and (2) the description of Sasak and Samawa people based on the folktales. The folktales used as data are (1) Batu Goloq (Sasak) and Batu Plantolan (Samawa); Mandalika (Sasak) and Lala Buntar (Samawa); and (3) Tegodek dait Tetuntel (Sasak) and Ne Bote Ne Kakura (Samawa). Data are gathered through library research. Problems are answered using Levi-Strauss structural theory saying that tale is the gate of understanding the people. It is found that the relation of each group of tales shows a consistency in similarities and differences. Batu Goloq and Batu Plantolan give a description that Sasak people tend to solve problems by themselves as a consequence of being closed people, while Samawa people tend to invite others in solving their problems as a consequence of  being  opened people. The similar characters found in Mandalika and Lala Buntar specifically in miteme processing, in taking decision, and solving problems. Mandalika is characterized as a closed figure, while Lala Buntar is an opened one in deciding and solving the problems. The comparison between Tegodek dait Tetuntel and Ne Bote Ne Kakura shows that Sasak and Samawa people tend to protest any mistreatment from high class community toward a lower class community. It is the manifestation of the same view toward refusal and disagreement to the oppression done by high status people.